The study of properties of a raw meat product during salting by brines - Shevchenko (Kishenko), Iryna; Donets, Oleksandr V.; Kryzhova (Vengliyk), Julia (My University, 2014)
The mechanism of forming of the coloured descriptions of the model meat systems is investigational with low maintenance of myoglobin on the stage of salting on the change of the coloured descriptions of meat raw material in the process of salting. Досліджено механізм формування кольорових характеристик модельних м'ясних систем із низьким вмістом міоглобіну на стадії соління на зміну кольорових характеристик м'ясної сировини в процесі соління.
Keywords: pigment; myoglobin; meat; brine; colour; пігмент; м'ясо; міоглобін; розсіл; колір; пигмент; миоглобин; мясо; рассол; цвет; кафедра технології м’яса і м’ясних продуктів